Thrombus in the Right Coronary Sinus of Valsalva Originating From the Left Atrial Appendage Causing Embolic Inferior Wall Myocardial Infarction - Hossam Abubakar MD; Ahmed S. Ahmed MD; Ahmed Subahi MD; Ahmed S. Yassin MD (SAGE Publishing, 2018)
Acute myocardial infarction (MI) is commonly a result of coronary atherosclerotic plaque rupture and superimposed thrombus formation. Nevertheless, uncommon causes of MI including embolism from aortic root and ascending aorta mural thrombi must be considered when coronary atherosclerotic disease is not evident. We report a case of a 84-year-old woman who presented with an inferior ST-segment elevation MI. Initial attempts to engage the right coronary artery (RCA) were unsuccessful. Aortic angiography revealed evidence of the left coronary artery ostium with absence of the right coronary ostium or RCA. Probing with a coronary wire where the RCA ostium was presumed to be located yielded resolution of the ST-segment elevation. The RCA was then easily engaged using a guide catheter, and angiographic evaluation showed a smooth vessel with no evidence of coronary artery disease except for abrupt termination of the distal PL2 branch. Contrast-enhanced computed tomography revealed an aortic root thrombus extending into the right coronary sinus of Valsalva and a thrombus in the left atrial appendage. The case reveals RCA embolism from an aortic root thrombus likely originating from the left trial appendage. A conservative approach to treatment with anticoagulation was pursued that resulted in full recovery. A review of the literature revealed that the etiology of aortic root thrombi is proposed to be multifactorial. Prospective randomized studies are needed to demonstrate the best treatment approach, although this appears to be impracticable given the rarity of the disease.